Lack of association between RAD50-IL13 polymorphisms and pediatric asthma susceptibility in Northeastern Han Chinese. (7th February 2016) - Li, Tianxiao; Ren, Zhimin; Deng, Ying; Wang, Yi; Zhou, Hongbo
Abstract: Objective : RAD50-IL13 region has been recently identified as one of critical asthma susceptibility loci in genome-wide association studies, yet the role of these genetic variants or single-nucleotide polymorphisms (SNPs) in the risk of developing asthma in Northeastern Han Chinese remains largely unknown. Methods : We conducted an association study by genotyping four SNPs (rs2244012 and rs6871536 in RAD50 as well as rs1295686 and rs1800925 in IL13 ) in 652 asthmatic children and age-matched 752 healthy controls from Northeastern Han Chinese to evaluate the asthma susceptibility with each individual SNP using SNaPshot genotyping method. Results : We did not find the allele or genotype frequency distribution of four SNPs in RAD50-IL13 region which was significantly different between asthmatic children and controls ( p  > 0.05). Conclusions : Our findings first suggested that the variants in RAD50-IL13 region were not associated with asthma risk in Northeastern Han Chinese children.